THE PSYCHOLOGICAL EFFECT OF THE ASEAN ECONOMIC COMMUNITY (AEC) TOWARDS HUMAN RESOURCES DEVELOPMENT - REZA FAHMI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". Yet those countries have several characteristics that are key to the creation of the ASEAN Economic Community, among others: (a) Market and a single production base (b) The high level of competition among the ASEAN countries. (b) This area has a great opportunity to grow as a global market. (d) an integrated ASEAN countries total in the global market. Cooperation undertaken by the ASEAN Economic Community includes: development of human resources, development potential, On professional qualifications, intense consultation on macroeconomic policy and financial policy, measurement of financial measures, Measurement of trade balance, infrastructure and so on. Through this article we are expected to understand that, the existence of the ASEAN Economic Community should be seen having a significant value by stakeholders; National entrepreneurs, economic actors, and especially by policy makers. Whereas, the presence of the ASEAN Economic Community is identical with the idea of globalization is realistic to build economic inequality amongst the people of the world. Where the owner of capital in this case is the first world countries expand its market to third world countries or poor. While the poor country is only a buyer or user of the rich country's products. This gave rise to widespread economic inequality. Not only that, the presence of the ASEAN Economic Community should not be a form of attitude inferiority complex and distrust themselves from ASEAN countries, which is just trying to "follow" the establishment of the European Economic Community. With simple language we need to take action to color the existence of the ASEAN Economic Community and not to be a passive audience that awaits change. At the same time we need to guard against conflicts of interest that would be detrimental to the national interests of Indonesia as a nation-state.